2017
DOI: 10.1177/0308518x17696071
|View full text |Cite
|
Sign up to set email alerts
|

Muslims in Indian cities: Degrees of segregation and the elusive ghetto

Abstract: In India, the country with the third largest Muslim population in the world, residential segregation along religious lines has long been of concern. Many go so far as to speak of the large-scale 'ghettoization' of Muslims, a trend commonly attributed to the state's negligence towards this religious minority and prolonged histories of so-called 'communal' violence between religious groups. Others emphasize long-standing pattern of residential clustering in enclaves and claim that these have always been voluntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…First, there are some spaces such as Juhapura and Sarkhej in Ahmedabad (Jaffrelot & Thomas, 2012;Thomas, 2017), Shivaji Nagar in Mumbai (Mhaskar, 2013), and Zakir Nagar in Delhi which have been identified as "ghettos" that were formed when Muslims were "targeted, thrust, and maintained in marginal locations" (Kirmani, 2008). Second, there is also evidence of long-standing patterns of residential clusterings called "enclaves," where one particular religious community decides to acquire exclusive ownership in order to establish their distance from the other religious communities (Susewind, 2017).Various scholars claim that there are many factors that lead to the formation of residential segregation including but not limited to the pull effects of economic clusterings (Galonnier, 2015;Jaffrelot & Thomas, 2012), the role of divisive identity politics based on religious identities of the citizens (Gupta, 2015;Seabrook & Siddiqui, 2015), and the unaddressed security concerns of the minority communities in riot-prone areas (Heitzman, 2008).…”
Section: Religious Segregation Of Residential Spaces In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…First, there are some spaces such as Juhapura and Sarkhej in Ahmedabad (Jaffrelot & Thomas, 2012;Thomas, 2017), Shivaji Nagar in Mumbai (Mhaskar, 2013), and Zakir Nagar in Delhi which have been identified as "ghettos" that were formed when Muslims were "targeted, thrust, and maintained in marginal locations" (Kirmani, 2008). Second, there is also evidence of long-standing patterns of residential clusterings called "enclaves," where one particular religious community decides to acquire exclusive ownership in order to establish their distance from the other religious communities (Susewind, 2017).Various scholars claim that there are many factors that lead to the formation of residential segregation including but not limited to the pull effects of economic clusterings (Galonnier, 2015;Jaffrelot & Thomas, 2012), the role of divisive identity politics based on religious identities of the citizens (Gupta, 2015;Seabrook & Siddiqui, 2015), and the unaddressed security concerns of the minority communities in riot-prone areas (Heitzman, 2008).…”
Section: Religious Segregation Of Residential Spaces In Indiamentioning
confidence: 99%
“…In India, which has the third largest Muslim population in the world, clustered living in neighborhoods defined by community, occupation, and endogeneity has a long history (Susewind, 2017). Among these different kinds of residential clustering, segregation on the basis of religious identities (Hindus-Muslims) is increasingly perceived as problematic witnessing prolonged instances of "communal violence" between religious groups, and the resulting prejudices and security concerns (Gayer & Jaffrelot, 2012).…”
mentioning
confidence: 99%
“…Haque (2016) too derived similar conclusions for West Bengal's 10 most populated cities analysing neighbourhood-level census data. Susewind (2017), studying Muslim segregation patterns in 11 select Indian cities, opined that cities marked by Muslim 'ghettoization' can have either very strong (Ahmadabad) or quite average (Mumbai and Aligarh) segregation extents. By developing a 'generalized poverty segregation curve', Dhongde (2017) found that a significant rise in the segregation of the poor over time in India.…”
Section: Towards An Articulation Of Segregation Studies In Urban Indiamentioning
confidence: 99%
“…However, this condition is not yet ideal because it does not solve the problem of segregation based on religion, namely, Islam and Christian. Religious segregation is the main element that results in increasing alienation, misunderstanding, cultural conflict, and even violence among believers of different faiths (Hu et al, 2019;Susewind, 2017). This was exacerbated by increasing populism and identity politics before, during, and after the Indonesia presidential elections in 2014 and 2019.…”
Section: Introductionmentioning
confidence: 99%